Recognising, understanding and managing endometriosis - Ian S Fraser (Wolters Kluwer Medknow Publications, 2008)
Endometriosis is defined as the presence of tissue lesions or nodules, histologically similar to the endometrium, at sites outside the uterus. It is a highly variable condition that has a wide spectrum of symptoms. The aetiology of endometriosis is probably multifactorial, with a strong familial component recognised. Women with endometriosis have multiple disturbances of function in the eutopic endometrium that women without the disease do not have. A firm diagnosis of endometriosis is rarely possible in general practice. The 'gold standard' for the diagnosis of pelvic endometriosis is currently a diagnostic laparoscopy.